EKSPRESI KEAGAMAAN MASYARAKAT PINGGIR KOTA (Studi Kasus di Cimenyan Bandung) - Irfan Setia Permana; Lukman Hamid (al-Afkar, Journal For Islamic Studies, 2021)
This study departs from the assumption that a society that is transitioning from a technological perspective will affect its religious attitude. The research was conducted at the Parukuyan Community in the Ciburial Village, Cimenyan District, Bandung Regency. This research uses qualitative methods with sociological and anthropological approaches. The theory used is Emile Durkheim's theory about the nature of religious experience. The results showed that: 1. The parukuyan community followers belong to religious groups, this is evidenced by the parukuyan followers in the divine aspect who believe in God as the ruler of the universe, however, in this divinity parukuyan followers practice religious syncretism in their beliefs. ; 2. In the aspect of message bearers and propagators of religion, parukuyan followers believe in prophethood as an intermediary from God to convey religious teachings to mankind, and also parukuyan followers respect guardians as the successors of prophets and spreaders of religious teachings; and 3. In the socio-cultural aspects such as radicalism and tolerance, followers of the Parukuyan association appreciate the diversity of humans in various aspects and are believed that this diversity is a necessity that everyone should respect.